Proceedings of the 3rd ACM Symposium on Computing for Development 2013
DOI: 10.1145/2442882.2442913
|View full text |Cite
|
Sign up to set email alerts
|

Health education in rural communities with locally produced and locally relevant multimedia content

Abstract: Health education in rural communities is one of the main ways in which developing countries are addressing prevalent health issues like maternal and child mortality, HIV/Aids, tuberculosis (TB) and malaria. In many rural villages, Community Health Workers (CHWs) act as proxies through which health education information is spread in their communities. In this paper, we discuss important principles to consider when designing solutions for creating and distributing digital health content in rural communities, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…While education videos are less personal, they are more accessible. Educational videos promise to reach a wider audience, including those living in hard-to-reach rural areas [17,22]. Educational videos are customizable, and information can be translated into various languages to increase accessibility further [15].…”
Section: Discussionmentioning
confidence: 99%
“…While education videos are less personal, they are more accessible. Educational videos promise to reach a wider audience, including those living in hard-to-reach rural areas [17,22]. Educational videos are customizable, and information can be translated into various languages to increase accessibility further [15].…”
Section: Discussionmentioning
confidence: 99%
“…The ASHAs receive 23 days of training in the first year, followed by 12 days of training in every subsequent year to keep them updated with the knowledge and skills needed to effectively perform their roles and responsibilities. Previous studies have identified many challenges in the training of ASHAs, such as lack of regular refresher training [ 32 ], shortage of competent trainers, insufficient funds, and use of obsolete health information [ 33 ]. The training programs have mostly been didactic-based and had limitations in the engagement of participants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many rural areas, health center staff attempt to spread information and awareness through a proper plan for health education (13). Health education is recognized as one of the most important approaches to eliminate knowledge gaps under the turbulent conditions of social opportunities in rural communities.…”
Section: Capacity-buildingmentioning
confidence: 99%